THE NEXUS BETWEEN BOARD COMPOSITION AND FIRM PERFORMANCE: EVIDENCE FROM THE F4GBM INDEX - Debbie James, Belawan; Chee Ling, Chin (UNIMAS Publisher, 2025)
This study examines the nexus between board composition and firm performance among companies listed under the FTSE4Good Bursa Malaysia (F4GBM) Index. A total of 116 F4GBM-listed companies were analyzed over a five-year period from 2019 to 2023 using panel data regression. Board composition was proxied by board size, board independence, and board gender diversity, while firm performance was measured by return on assets (ROA) and return on equity (ROE). The empirical results indicate that none of the board composition variables have a statistically significant impact on firm performance. However, the control variables show significant effects—debt ratio negatively influences performance, while firm size exhibits a positive relationship. The insignificant findings suggest that, among Malaysian ESG-compliant firms, the influence of board structure on financial performance may be limited due to standardized governance practices and regulatory requirements under Bursa Malaysia’s corporate governance framework.